DEVELOPMENT OF SMART LADDER MEDIA ASSISTED BY KOLINTANG MUSICAL INSTRUMENTS TO INCREASE THE LEARNING INTEREST OF GRADE I STUDENTS - Tasya Wulandari; Sukmawarti Sukmawarti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
This study aims to develop smart ladder media assisted by kolintang musical instruments, determine the feasibility and interest in learning class I students at SD IT Bustanul Ulum, especially in mathematics subjects in the 2022-2023 Learning Year, especially in mathematics subjects. The research method used was a pretest and posttest conducted to measure the feasibility of the learning media developed. The results of the study revealed that the development of learning media in the form of smart ladder media assisted by kolintang musical instruments was declared feasible based on data analysis obtained through the validity test of material experts, media design experts, teacher responses, and student responses, the average was calculated to obtain a result of 84.2%, including in the category of very good / very feasible to use in the learning process. Based on the results of the pretest and posttest that have been carried out, there is an increase in student interest and learning outcomes before and after using smart ladder media assisted by kolintang musical instruments on addition and subtraction material that has been developed by 12% so that it can increase interest and affect the learning outcomes of grade I elementary school students